2016
DOI: 10.31018/jans.v8i1.788
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis and inbreeding depression to identify superior F1 hybrids in tomato (Solanum lycopersicum L.) for the yield and its contributing traits

Abstract: Eight parental lines of diverse origin of tomato (Solanum lycopersicum L.) were crossed in 8 × 8 diallel mating design excluding reciprocals. The 28 F1 hybrids along with their parents and one standard check (H-86) were evaluated in a randomized block design with three replications during seasons of rabi 2011-12, 2012-13 and 2013-14. In the present study, revealed that heterosis over better parent, mid parent, standard check and inbreeding depression was observed for all the traits under studies. Highly signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 2 publications
2
5
0
Order By: Relevance
“…Significant positive heterosis has been reported by Ahmad et al [6], and Sharma et al [20]. These findings of significant positive heterosis over mid and better parent are in line with the findings of Singh et al [5] and Kumar and Singh [25] as well.…”
Section: Fruit Length (Cm)supporting
confidence: 85%
See 1 more Smart Citation
“…Significant positive heterosis has been reported by Ahmad et al [6], and Sharma et al [20]. These findings of significant positive heterosis over mid and better parent are in line with the findings of Singh et al [5] and Kumar and Singh [25] as well.…”
Section: Fruit Length (Cm)supporting
confidence: 85%
“…Bhatt et al [8,27] observed 2.92 to 54.17% better parent heterosis for yield per plant in tomato, which is very identical to our findings. Similarly, heterobeltiosis in tomato hybrids was also reported in many studies [3,6,14,25,26,29,30]. Therefore, these genotypes may be selected as heterotic hybrids for yield and can further be advanced toward developing a high yielding variety.…”
Section: Fruit Yield Per Plant (Kg)mentioning
confidence: 66%
“…Four cross combinations were found superior than the standard check (1350 g) for this trait. Similar estimates for this trait were also reported by Singh and Sastry, (2011) and Kumar and Singh (2016). Plant height is one of the most important factors that determines the harvest duration of the indeterminate tomatoes.…”
Section: Resultssupporting
confidence: 86%
“…HASSAN et al average fruit weight (Stommel, 2001;Rodríguez et al, 2010) and TSS (Rodríguez et al, 2010). Also, Bhnan (2002) and Kumar & Singh (2016) reported that the inbreeding depression (ID) in some produced hybrids was not significant for yield and fruit quality. However, this approach has not been discussed in earlier studies.…”
Section: Introductionmentioning
confidence: 99%